If f(x) = 3x and g(x) = 3(x + 1) + 6. Describe the Transformations from f(x) to g(x).

left 1 and up 6

left 6 and up 1

right 6 and up 1

right 1 and down 6
We will be using the formula of transformations to solve this.
Answer: If f(x) = 3x and g(x) = 3(x + 1) + 6, then the Transformations from f(x) to g(x) is left 1 and up 6.
Let's solve this step by step.
Explanation:
Given that, f(x) = 3x and g(x) = 3(x + 1) + 6
We have general formula of transformations as f(x) = a(bx − h)^{n} + k
where k is the vertical shift, h is the horizontal shift, a is the vertical stretch and b is the horizontal stretch.
On comparing g(x), we get h = 1 and k = 6
⇒ We are shifting 1 to the left and 6 up.